2010
DOI: 10.1002/chem.200903461
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Surfactant Density on SWCNTs by Analytical Ultracentrifugation

Abstract: We report on the extensive characterization of single-walled carbon nanotubes (SWCNTs) dispersed in a variety of surfactants, such as sodium dodecyl benzene sulfonate (SDBS), sodium cholate (SC), and three synthesized perylene-based surfactants, by using differential sedimentation in H(2)O and D(2)O. Multidimensional evaluation of the absorption profiles over radius, wavelength, and time allows the determination of the anhydrous specific volumes of the SWCNT-surfactant complexes as well as the concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 40 publications
2
38
1
2
Order By: Relevance
“…As previously shown by Hersam and co-workers, [ 105 ] the hydrodynamic characterization of surfactant encapsulated SWCNTs by analyzing the differential sedimentation of the colloids in water and deuterated water with the aid of analytical ultracentrifugation is a highly versatile route to determine packing densities of the surfactant on the nanotube surface. In a similar manner, the adsorption behavior of our designed perylene-based surfactants was investigated [ 97 ] and completely in line with the results obtained from zeta potential and absorption spectroscopy investigations, [ 89 ] as well as replacement titrations, [ 91 ] we demonstrated that the sterically demanding bolaamphiphile 2 is least densely arranged on the nanotube scaffold. The smaller bolaamphiphile 1 bearing two fi rst generation Newkome -type dendrimers in the periphery exhibits slightly lower packing densities than the amphiphile 3 being equipped with one second generation Newkome -type dendrimer and a long aliphatic chain.…”
Section: Progress Reportsupporting
confidence: 77%
See 1 more Smart Citation
“…As previously shown by Hersam and co-workers, [ 105 ] the hydrodynamic characterization of surfactant encapsulated SWCNTs by analyzing the differential sedimentation of the colloids in water and deuterated water with the aid of analytical ultracentrifugation is a highly versatile route to determine packing densities of the surfactant on the nanotube surface. In a similar manner, the adsorption behavior of our designed perylene-based surfactants was investigated [ 97 ] and completely in line with the results obtained from zeta potential and absorption spectroscopy investigations, [ 89 ] as well as replacement titrations, [ 91 ] we demonstrated that the sterically demanding bolaamphiphile 2 is least densely arranged on the nanotube scaffold. The smaller bolaamphiphile 1 bearing two fi rst generation Newkome -type dendrimers in the periphery exhibits slightly lower packing densities than the amphiphile 3 being equipped with one second generation Newkome -type dendrimer and a long aliphatic chain.…”
Section: Progress Reportsupporting
confidence: 77%
“…[ 75 ] Based on these observations, it is proposed that the amphiphilic PBI adsorbs on the nanotube surface in such a way that the solvophylic head and the lipophylic tail alternate to allow maximum loading. [ 97 ] As imaged by atomic force microscopy in phase imaging the nanotubes are accordingly more homogenously covered by PBI 3 compared to the bolaamphiphiles (Figure 4 b). [ 89 ] As also demonstrated by other groups [ 106,107 ] the homogeneity of the SWCNT coverage directly impacts the fl uorescence quantum yields of the carbon allotrope, presumably due to the reduced contact with water and oxygen.…”
Section: Progress Reportmentioning
confidence: 95%
“…[13][14][15][16][17] In contrast, there have been limited studies into the suitability of different classes of other small molecules for dispersing CNTs. Our goal is to produce new membrane materials that are highly permeable to water, and able to discriminate between different dissolved solutes.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain insights into the adsorption geometry, we performed analytical ultracentrifugation (AUC) in water and deuterated water, because the anhydrous molar specific volume of the SWCNT-surfactant complex can be derived from the sedimentation coefficients. [32][33] The anhydrous specific volume was determined for the HiPco-2 and CoMoCAT-2 complexes, and for HiPco-SC (SC = sodium cholate) and CoMo-CAT-SC for comparison (Table 2). …”
mentioning
confidence: 99%
“…This is in complete agreement with results published elsewhere. [32] In summary, the repeated titrations have yielded useful information about the interaction of the perylene dispersants with the nanotubes. Most importantly, it is shown that the perylene derivatives are first replaced from larger-diameter nanotubes (9,5), followed by medium (7,6), and then smaller-diameter nanotubes (7,5).…”
mentioning
confidence: 99%